Congregational Worshiping and Implementation of the COVID-19 Preventive Behavioral Measures During the Re-opening Phase of Worship Places Among Indonesian Muslims - Nurmansyah, Mochamad Iqbal (Journal of religion and health, 2022)
This research aimed at exploring the congregational form of worshiping and the preventative behaviors against COVID-19 among Indonesian Muslims during the re-opening phase of worship places. One thousand and ninety-seven (1097) participants who were a part of one of the largest Indonesian socio-religious organizations (Muhammadiyah) were included in the study. This study found most of the respondents to have performed tarawih prayers (66.7%) and Eid prayers (67.4%) at home during the pandemic. Furthermore, some Muslim worshipers did not observe COVID-19 preventive behavioral measures during the congregational prayers, and the attended mosques had inadequate facilitation for COVID-19 prevention. Neverthless, mosques are important settings for health promotion programs, whose religious leaders can be partners in delivering health related messages to their attending members.